Components of the Public Budget and their Effects on Public Debt in Jordan - Qwader, Amjad S.; Aloshaibat, Sulieman D. (International Journal of Economics and Financial Issues, 2020)
This study aims to identify the role of the main components of the public budget for influencing public debt in Jordan through an econometric study. In particular, the EViews 9 program is applied to the annual time series of public debt, current expenditures, capitalism expenditures, taxes, and external grants from 1990 to 2018. Results are related to the data that served as basis of this study and was issued by the Central Bank of Jordan. This study concludes a set of results, including the presence of a positive and moral effect of capital spending on public debt and the presence of a negative and moral effect of taxes on public debt in short and long terms. Results show a positive and significant effect of the current spending on public debt in the short term and a positive, nonsignificant effect in the long term. In addition, a negative, non-significant influence of external grants on public debt in the short term and a negative moral effect in the long term are found. A set of recommendations is presented. First, mechanisms to reduce waste in public budget should be activated, particularly in the area of current expenditures, through addressing administrative sagging in the public sector. Thus, employment is linked to the level of future productivity. Second, corruption and nepotism should be fought against. Third, transparency should be imposed in state departments. Keywords: capital expenditures, current expenditures, external grants, general budget, public debt, taxes. JEL Classifications: H6, H63, H72 DOI: https://doi.org/10.32479/ijefi.9717